Determining optimal follow‐up in the management of human papillomavirus‐positive oropharyngeal cancer. Issue 4 (13th November 2015) - Frakes, Jessica M.; Naghavi, Arash O.; Demetriou, Stephanie K.; Strom, Tobin J.; Russell, Jeffery S.; Kish, Julie A.; McCaffrey, Judith C.; Otto, Kristen J.; Padhya, Tapan A.; Harrison, Louis B.; Trotti, Andy M.; Caudell, Jimmy J.
Abstract : BACKGROUND: Determining the optimal follow‐up for patients can help maximize the use of health care resources. This is particularly true in a growing epidemic such as human papillomavirus‐positive oropharyngeal squamous cell carcinoma (HPV+OPSCC). The objective of the current study was to evaluate time to disease recurrence or late toxicity in this cohort of patients to optimize patient management. METHODS: An institutional database identified 232 patients with biopsy‐proven, nonmetastatic HPV+OPSCC who were treated with radiotherapy. A retrospective review was conducted in patients who were followed every 3 months for the first year, every 4 months in year 2, and every 6 months in years 3 to 5. Late toxicity (grade ≥ 3; toxicity was scored based on National Cancer Institute Common Terminology Criteria for Adverse Events [version 4]), locoregional control, distant control, and overall survival were assessed. RESULTS: The median follow‐up was 33 months. Based on Radiation Therapy Oncology Group (RTOG) 0129 study risk groupings, patients were either considered to be at low (162 patients; 70%) or intermediate (70 patients; 30%) risk. Concurrent systemic therapy was used in 85% of patients (196 patients). The 3‐year locoregional control, distant control, and overall survival rates were 94%, 91%, and 91%, respectively. Late toxicity occurred in 9% of patients (21 patients). Overall, 64% of toxicity and failure events occurred within the first 6 months of follow‐up, with a < 2% event incidence noted at each subsequent follow‐up. Only 4 patients experienced their first event after 2 years. CONCLUSIONS: HPV+OPSCC has a low risk of disease recurrence and late toxicity after treatment; approximately two‐thirds of events occur within the first 6 months of follow‐up. These data suggest that it may be reasonable to reduce follow‐up in patients with HPV+OPSCC to every 3 months for the first 6 months, every 6 months for the first 2 years, and annually thereafter. Cancer 2016;122:634–641. © 2015 American Cancer Society . Abstract : Human papillomavirus‐positive oropharyngeal cancer has a low incidence of failure and toxicity with modern treatment techniques, with the majority of events occurring within the first 6 months of follow‐up. Optimizing management in this rapidly growing population may be achieved by deescalation of follow‐up intensity.